2014
DOI: 10.7314/apjcp.2014.15.9.3965
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Breast Cancer Screening among Iranian Women without Experience of Mammography: A Qualitative Study

Abstract: Background: In Iran, there are high rates of breast cancer. It is among the five most common cancers, the first among cancers diagnosed, and is the leading cause of cancer deaths among Iranian women. Objectives: The purpose of this qualitative study was to explore perception of breast cancer screening among Iranian women who have never had a mammograph. Materials and Methods: The current study was part of a qualitative research conducted by means of content analysis method and purposive sampling of 16 women ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
24
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 25 publications
4
24
0
1
Order By: Relevance
“…This study found several inhibiting factors for the mammography screening including high cost, limited access, and lack of urgency. A qualitative study conducted in Iran also found several inhibiting factors which are similar to our findings in addition to the public perception of the test being inessential and expensive and the lack of mammography centers [20]. Meanwhile, another study in Sweden revealed a different main inhibiting factor: the examination itself raised concerns about breast cancer [18].…”
Section: Discussionsupporting
confidence: 85%
“…This study found several inhibiting factors for the mammography screening including high cost, limited access, and lack of urgency. A qualitative study conducted in Iran also found several inhibiting factors which are similar to our findings in addition to the public perception of the test being inessential and expensive and the lack of mammography centers [20]. Meanwhile, another study in Sweden revealed a different main inhibiting factor: the examination itself raised concerns about breast cancer [18].…”
Section: Discussionsupporting
confidence: 85%
“…Multiple risk factors may enhance the odds of developing breast cancer, but lifestyle factors seem to have a larger impact on it. Prevention has been proposed as an effective method to reduce the burden of breast cancer [4, 5]. Furthermore, a health-promoting lifestyle has been recommended for breast cancer prevention [6].…”
Section: Introductionmentioning
confidence: 99%
“…It is the most prevalent type of cancer afflicting Iranian women (24.85%) . Iranian women tend to be affected a decade earlier than women in developed countries; the most common age of diagnosis is 47 years . The high incidence of this cancer in Iran means that many families have members with breast cancer …”
Section: Introductionmentioning
confidence: 99%